Turkish and Iranian attitudes toward Political changes in Middle East (Journal of the College of Education for Women, 2019)
There are many developments in political, strategic aspects in the middle east either ininternational field which represented by U.S.A as first polar in world or territorial field whichrepresent by Turkey and Iran, as territorial powers in the region, Turkish role is fit withAmerican position in order to draw new map of middle east, Turkey advocate new policy toconfirm its attitude in Euro peen Union and its relation with U.S.A.Iran adopted policy of Expansion in Iraq, Yamen, Lebanon and Syria, in addition Iranenlist all it efforts to develop its Nuclear program and enter Nuclear club which make Iran,Super power in middle east and the world, each Turkey and Iran have certain attitudes towardall political changes in middle east and employ changes for their interests.